Cobenefits and trade-offs of green and clean energy: Evidence from the academic literature and Asian case studies - Benjamin K. Sovacool (Asian Development Bank (ADB), 2016)
This working paper assesses the positive cobenefits of promoting green and clean energy in Asia. It first defines what is meant by "clean" energy across the four technological systems of cooking, renewable electricity, energy efficiency, and urban transport. Then, drawn from a synthesis of peer-reviewed articles, it summarizes at least four general types of cobenefits of investing in these systems: (i) diversification and enhanced energy security, (ii) jobs and green growth, (iii) displaced pollution and associated cost savings, and (iv) enhanced resilience and adaptive capacity to things like climate change and natural disasters. It also offers some insight to possible challenges and trade-offs that must be managed when attempting to capture cobenefits. The paper then focuses on four case studies of cobenefits that have been delivered in practice: liquefied petroleum gas stoves in Indonesia, renewable electricity generation in the People's Republic of China, energy efficiency in Japan, and mass transit in Singapore. The paper concludes with insights for energy analysts and policy makers.
Keywords: Q54; 330; climate change